2011
DOI: 10.1007/s11325-011-0627-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and polysomnographic data of positional sleep apnea and its predictors

Abstract: Positional OSA is very prevalent and noted in almost 70% of our patients. Low snoring frequency was noted to be a positive predictor for positional OSA, contrarily to low mean oxygen saturation which was found to be a negative predictor. These findings are encouraging that positional therapy can be very beneficial as the treatment modality for OSA among Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 26 publications
2
31
2
6
Order By: Relevance
“…Although earlier studies reported the AHI as negative predictor for POSA [12,13,[20][21][22], this was not found in the current study. Additionally, neck circumference appeared no predictor in current analysis, whereas contrasting results were published by Mador et al and Teerapraipuk et al [12,22]. Although five univariate variables reached a significance level below 0.2 in this study, only two were significant in multivariable analysis.…”
Section: Predictive Factors Posacontrasting
confidence: 95%
See 1 more Smart Citation
“…Although earlier studies reported the AHI as negative predictor for POSA [12,13,[20][21][22], this was not found in the current study. Additionally, neck circumference appeared no predictor in current analysis, whereas contrasting results were published by Mador et al and Teerapraipuk et al [12,22]. Although five univariate variables reached a significance level below 0.2 in this study, only two were significant in multivariable analysis.…”
Section: Predictive Factors Posacontrasting
confidence: 95%
“…An AHI of 0-5 states no OSA, whereas scores of [5][6][7][8][9][10][11][12][13][14][15][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and ≥30 state mild, moderate, and severe OSA, respectively [5,9]. In the case of moderate or severe OSA, continuous positive airway pressure (CPAP) therapy is prescribed [10].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This proportion in even higher in Asian patients. [3][4][5] Compared to patients without position dependence, these patients tend to be less obese, younger, with better sleep quality and less daytime sleepiness. 6 It has been argued that since most obstructive sleep apnea (OSA) patients have mild to moderate severity and since position dependence is most prevalent in these categories, the great majority of patients with sleep-disordered breathing demonstrate this phenotype.…”
mentioning
confidence: 99%
“…12 The prevalence of POSA is thought to be higher in Asian populations. 13,14 Most but not all PP still snore when sleeping in the lateral posture, but their sleep is interrupted with only a few apneas or hypopneas or not at all, and they consequently achieve a better sleep quality.…”
Section: Efficacy Of the New Generation Of Devices For Positional Thementioning
confidence: 99%